Stages of development of Lenin Street in Chita - Semushina Irina S.; Bazilevich Mikhail E. (Архитектон)
The article reviews the process of development of Lenin Street, the central street of the city of Chita. The study has identified five key stages in the formation of the street’s architectural ensemble, defined by the general historical processes that took place in the region and the specifics of the development of the city itself. Individual objects of historical and architectural heritage that form an integral part of the city’s cultural identity are described.